AESTHETIC NATURE OF RADIF IN FOLK SONGS - Layla Omonovna Torayeva (Journals Park Publishing, 2024)
Uzbek folk songs appear as a unique poetic system with their specific meaning and melody. Radif is one of these poetic repetitions, which serves to form the rhythm of the song and to deeply understand its content. The article discusses the expression of radif in folk songs and its aesthetic nature.
Keywords: Radif, rhyme, aruz weight, finger weight, word repetition, musicality, melody, rhythm, title.